Videomicroscopy reveals individual response of MCF7 cells to X-ray irradiation - Joséphine Courouble; Stéphane Plaszczynski; Olivier Seksek (PLoS ONE, 2026)
Understanding the heterogeneity of cellular responses to irradiation is a key factor in cancer research to improve radiotherapy efficacy. To this aim, time-lapse 2D videomicroscopy was used to track in vitro more than 6 300 individual MCF7 breast cancer cells exposed to single X-ray irradiation, with doses ranging from 0 Gy to 5 Gy. Cell tracking and lineage reconstruction were performed using a dedicated algorithm: Cell Lineage Tracking (CLT). The CLT algorithm achieves high robustness and reliability across irradiation conditions, with more than 95% correct lineage tree assignment and over 80% agreement in reconstructed cell cycle duration. It allowed classification and study of the properties and fates of different cell categories (proliferative, transiently arrested and long-term arrested) and revealed distinct behavior, notably in individual cell surface area and diffusion properties. Cell surface area increased progressively across cell categories, from approximately 5 000 μ m 2 in proliferative cells to about 50 000 μ m 2 in long-term arrested cells, with transiently arrested cells showing intermediate values and their daughter cells approaching those of proliferative cells. Cell surface also increased with higher doses within each cell category. In contrast, diffusion decreased across cell categories, from around 0.4 μ m 2 / h in proliferative cells to around 0.02 μ m 2 / h in long-term arrested cells, with transiently arrested cells showing intermediate diffusion and their daughter cells approaching the dynamic behavior of proliferative cells. Within each cell category, diffusion did not show a clear dependence on dose. This novel single-cell and lineage-level framework highlights the importance of dynamic analyses in uncovering the complexity and heterogeneity of radiation responses.